Perbedaan Kebutuhan Ruang Terbuka dan Fasilitas Penunjangnya Sesuai Kebutuhan Warga Permukiman Tepian Sungai Musi, Kota Palembang, Sumatera Selatan - Listen Prima; Harrini Mutiara Hapsari; Sindy Daisy Cahyany; Nurhasanah; Indah Nurlia Afiyah; Chiquita Mutiara Ananda; Rayhan Haris Maulana; Syamsul Maarif (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2023)
Open space is an important element inherent in the community along the Musi River in activities or activities of daily life as a place for gathering, chatting, playing, shopping or just sitting. The need for open space is influenced by various aspects, one of which is the difference in needs according to community groups (age). The importance of the need for types of open space and open space supporting facilities is the background of this research, to determine the different types of open space and supporting facilities needed by the community to support daily activities or activities based on community groups (age). This research was conducted using quantitative methods to process three types of data which were the result of questionnaires and surveys, such as: the type of open space that is often used; the facilities needed; and the type of open space needed. The three types of data are processed through the JMP application. Descriptive method is used to explain the results of the analysis regarding the types of open space and facilities needed by the community on the banks of the Musi River. The results of the study indicate that there is an influence of community groups (age) which is more directed to the open space facilities needed and supported by fairly complex needs, as well as the situation and condition of the settlements occupied according to age groups, namely children, adolescents, and adults.